Reference state, structure, regime shifts, and regulatory drivers in a coastal sea over the last century: The Central Baltic Sea case. Issue Volume 67:Issue S1(2022)Special issue (19th November 2021) - Tomczak, Maciej T.; Müller‐Karulis, Bärbel; Blenckner, Thorsten; Ehrnsten, Eva; Eero, Margit; Gustafsson, Bo; Norkko, Alf; Otto, Saskia A.; Timmermann, Karen; Humborg, Christoph
Abstract: The occurrence of regime shifts in marine ecosystems has important implications for environmental legislation that requires setting reference levels and targets of quantitative restoration outcomes. The Baltic Sea ecosystem has undergone large changes in the 20 th century related to anthropogenic pressures and climate variability, which have caused ecosystem reorganization. Here, we compiled historical information and identified relationships in our dataset using multivariate statistics and modeling across 31 biotic and abiotic variables from 1925 to 2005 in the Central Baltic Sea. We identified a series of ecosystem regime shifts in the 1930s, 1970s, and at the end of the 1980s/beginning of the 1990s. In the long term, the Central Baltic Sea showed a regime shift from a benthic to pelagic‐dominated state. Historically, benthic components played a significant role in trophic transfer, while in the more recent productive system pelagic–benthic coupling was weak and pelagic components dominated. Our analysis shows that for the entire time period, productivity, climate, and hydrography mainly affected the functioning of the food web, whereas fishing became important more recently. Eutrophication had far‐reaching direct and indirect impacts from a long‐term perspective and changed not only the trophic state of the system but also affected higher trophic levels. Our study also suggests a switch in regulatory drivers from salinity to oxygen. The "reference ecosystem" identified in our analysis may guide the establishment of an ecosystem state baseline and threshold values for ecosystem state indicators of the Central Baltic Sea.